GOLD SOLUBILITY AND SPECIATION IN HYDROTHERMAL SOLUTIONS: EXPERIMENTAL STUDY OF THE STABILITY OF HYDROSULPHIDE COMPLEX OF GOLD (AUHS°) AT 350 TO 450°C AND 500 BARS - Gibert F.; Pascal M.L.; Pichavant M. (My University, 1998)
The solubility of gold was measured in aqueous KCl (0.5 m) solutions under oxygen, sulfur, and slightly acidic pH buffered conditions between 350 and 450°C at a constant pressure of 500 bars. Two buffer assemblages were used to constrain fO2, fS2, and consequently fH2 and aH2S: respectively, pyrite-pyrrhotite-magnetite (Py-Po-Mt) and pyrite-magnetite-hematite (Py-Mt-Hm). The measured solubility of gold at equilibrium with Py-Po-Mt and Qtz-KF-Mus is 52 ± 8 ppb at 350°C, 134 ± 17 ppb at 400°C and 496 ± 37 ppb at 450°C. With Py-Mt-Hm and Qtz-KF-Mus the solubility of gold is increased to 198 ± 9 ppb at 400°C and 692 ± 10 ppb at 450°C. These results are consistent with the aqueous complex AuHS° being the dominant gold-bearing species. The equilibrium constants (log KR10) for the reaction: have been determined at 350, 400, and 450°C and are, respectively, −5.20 ± 0.25, −5.30 ± 0.15, and −5.40 ± 0.15. These values are similar to those suggested by Zotov (written pers. commun.) and those obtained by recalculating the experimental data of Hayashi and Ohmoto (1991). They are significantly higher than those derived by Benning and Seward (1996) and the possible causes of the discrepancies are discussed.The equilibrium constant for AuHS° shows that this species plays an important role in the deposition of gold in natural environments. Cooling, H2S loss, pH change, and oxidation seem to be effective mechanisms for gold precipitation, depending on the local ore forming conditions.